(untitled) (Journal of Hama University, 2022)
The tested genetic material was collected from the germplasm available to farmers, especially from the Al-Ghab region, Idlib and Aleppo, where some local varieties for white corn (sorghum) with the desired white grain color are concentrated for farmers, and also from introduced strains from international centers that are interested in this crop within the framework of agricultural cooperation between the Ministry of Agriculture in Syria and among some countries such as Egypt, Sudan and India. The genetic material was selected on the basis of some formal characteristics that give initial indications of abundant grain yield, such as symmetry of plants and Head, plant height, height of Head, length of Head, color of seeds, shape of Head, leaf area, number of leaves, and many other formal and qualitative indicators of grains. In addition to the resistance to diseases and insects. Selection Mas method was implemented in the collection of these germplasm and individual selection in the breeding and selection program by the Pure line selection experiment, and also cross-breeding was carried out between the origins introduced from outside the country and the local strains within the manual crossbreeding experiment to derive the first generation and tested in several generations before introducing them to comparative experiments. Grain yield. The results showed the distinction of some strains compared with the controls approved in the country and used in comparison for rain-fed cultivation (Ezra-3 and Al-Razinia). Noting that these inputs retain important qualities in their grains, such as the content of oil, protein and starch. The results of the tests showed the importance of the superiority of these models in Syria and their suitability for rain-fed agriculture in the first and second stabilization areas, with the possibility of supplementary irrigation as models with desirable white grains and with an increase in the yield, which contributes to meeting the country’s need of this material.